Legal Liability of Shopee for AI Chatbot Misinformation in Consumer Protection: A Normative Juridical Analysis - Safitri, Rahmad; Azrica, Hanita; Muttaqin, Zainal; Hayani, Afla (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
The development of digital technology is expected to improve the quality of e-commerce services through innovations such as AI chatbots that provide fast, accurate, and responsive information. However, in practice, problems remain, particularly misinformation that may harm consumers and create uncertainty regarding legal liability. This study aims to analyze Shopee’s legal responsibility for misinformation delivered by AI chatbots from the perspective of consumer protection. The research method used is library research with a qualitative approach through normative juridical analysis, employing primary sources such as the Consumer Protection Act (UUPK), the Electronic Information and Transactions Act (UU ITE), and the Government Regulation on Electronic Systems and Transactions (PP PSTE), along with secondary sources including legal books, journals, and articles. The findings show that Shopee remains legally responsible since consumers are entitled to accurate, clear, and honest information under the Consumer Protection Act, and electronic system providers are obliged to maintain system reliability and security under the ITE Law and PP PSTE. Thus, legal responsibility lies with the platform provider rather than the AI system itself, highlighting the need for more adaptive regulations to ensure consumer protection in the digital era.